Research on the effects of resistance training on the special strength of judoists - Bratic, M.; Nurkic, M.; Kasum, G. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2005)
The physical fitness of athletes holds a significant place in achieving results in competitions in all areas of sport.Apart from the inexhaustible multitude of technical elements that judo possesses, the improvement of physical and functional abilities is a good basis for achieving top results. It is usual that the condition training of judoists is planned to incorporate three main phases, each of which is characterized by its own special dynamic: • phase one consists of the work involved in a training program which is aimed at the development of the so-called basic foundations (strength and endurance), which take up a great part of general many-sided training, • phase two requires a smaller amount of overall work, but a greater intensity of effort,in order to develop the so-called specific competitive foundations of judoists, • phase three of condition training builds up specificabilities,thecompetitors`agilityaswellasmotoricandsituational motoric skills. This research has as its aim to show the basic principles of the training process in the preliminary period, the application of the model for the training of the specific strength of judoists and the changes which take place due to the application of this training model, all during the period of time covered by this research. The research included judoists who participate in competitions at the national level. Six tests were used to check the special strength of judoists. The results of the research indicate that during the experimental treatment (the preliminary period), a statistically relevant increase in the special strength of judoists was detected by means of all the tests used for measuring it.